Analysis of Character Values in Grade 11 Civic Education Textbooks of the Merdeka Curriculum - Abdul Muktadir, ‎; Susanti, Atika; Irmayanti, Meiselina (KnE Social Sciences, 2025)
This study analyzes the basic principles of character education in the Merdeka Curriculum grade II student book in the revised edition of the Civics subject published in 2022. The urgency of this research lies in the importance of analyzing character values in textbooks as the main medium for early childhood student character building. This study uses a combination of qualitative research methods and content analysis. This research uses the Merdeka Curriculum grade II student book on Civics as the main book and data source. The data must be analyzed thoroughly and accurately to determine the educational characteristics of the book. Based on the results of the study, there is data on character education values obtained in the Merdeka Curriculum grade II student book in Civics subjects, including religion, independence, cooperation, national spirit, environmental care, social care, courtesy, responsibility, discipline, and honesty. The values of character education in the Civics subject are religion, independence, cooperation, national spirit, environmental care, social care, courtesy, responsibility, discipline, honesty, friendly/communicative, peace-loving, patriotism, fairness, global diversity, tolerance, love of reading, and love for the country which have included the characters that need to be instilled in students. This study successfully identified the character education values contained in the Merdeka Curriculum grade II student book in the Civic Education subject. Teachers are expected to integrate character education values into more contextual and interactive learning to maximize the implementation of these values. In addition, ongoing teacher training and regular evaluations are essential to ensure students can understand and apply these values on a daily basis.